2016
DOI: 10.1080/08865655.2016.1257365
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Border Collaboration in Economic Development: Institutional Change on the Anglo-Scottish Border

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines. Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and notforprofit activities provided that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Leick [ 46 ] also identified employee recruitment as a motivation for cross-border business interaction. However, motivations can shift in response to changed economic conditions and policy priorities [ 17 ], and cross-border business interaction of enterprises also depends on the size and industrial focus of the neighboring market which is also an indication of the importance of the economic environment [ 47 ]. Some Euregios have succeeded to act as a policy advisor in cross-border regions, while other multinational organizations still suffer from increased coordination costs [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leick [ 46 ] also identified employee recruitment as a motivation for cross-border business interaction. However, motivations can shift in response to changed economic conditions and policy priorities [ 17 ], and cross-border business interaction of enterprises also depends on the size and industrial focus of the neighboring market which is also an indication of the importance of the economic environment [ 47 ]. Some Euregios have succeeded to act as a policy advisor in cross-border regions, while other multinational organizations still suffer from increased coordination costs [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…institutional and policy changes [see also 6 , 51 ]. While cross-border business interaction fluctuated over time, Euregional institutions seem to have a positive impact on the level of cross-border business interaction [ 17 ]. An interplay of various stakeholders, such as enterprises, research organizations, and policy makers is important to facilitate knowledge flows across industries and hence to support innovation, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the insights concerning the CBRIS model are therefore derived from qualitative case studies. These studies include investigations into company-level cross-border innovation cooperation (van den Broek et al, 2018aBroek et al, , 2018b, the role of universities and non-profit organizations in cross-border integration (van den Broek et al, 2019;Cappellano and Makkonen, 2020b;Cappellano et al, 2020), the impact of institutional change and funding programmes on crossborder innovation cooperation (Peck and Mulvey, 2018;Makkonen et al, 2018b;Miörner et al, 2018) and the potential for adopting common cross-border innovation policies (Tõnurist and Kattel, 2017;Muller et al, 2017). These studies have shown that even CBRs with relatively high levels of (cognitive, cultural, institutional, social or geographical) proximity report low levels of cross-border innovation connections and integration, in contrast to what is suggested in the conceptual definition of a strongly integrated CBRIS by Lundquist and Trippl (2013).…”
Section: Critical Review Of the Cross-border Regional Innovation Syst...mentioning
confidence: 99%